The environmental dependence of the structure of galactic discs in STAGES S0 galaxies: implications for S0 formation - Maltby, David Terence; Aragón-Salamanca, Alfonso; Gray, Meghan E.; Hoyos, Carlos; Wolf, Christian; Jogee, Shardha; Böhm, Asmus (Oxford University Press, 2015)
We present an analysis of V-band radial surface brightness μ(r) profiles for S0 galaxies in different environments using Hubble Space Telescope/Advanced Camera for Surveys imaging and data from the Space Telescope A901/2 Galaxy Evolution Survey. Using a large sample of ∼280 field and cluster S0s, we find that in both environments, ∼25 per cent have a pure exponential disc (type I) and ∼50 per cent exhibit an up-bending disc break (antitruncation, type III). However, we find hardly any (<5 per cent) down-bending disc breaks (truncations, type II) in our S0s and many cases (∼20 per cent) where no discernible exponential component was observed (i.e. general curvature). We also find no evidence for an environmental dependence on the disc scalelength h or break strength T (outer-to-inner scalelength ratio), implying that the galaxy environment does not affect the stellar distribution in S0 stellar discs. Comparing disc structure (e.g. h, T) between these S0s and the spiral galaxies from our previous studies, we find: (i) no evidence for the type I scalelength h being dependent on morphology; and (ii) some evidence to suggest that the type II/III break strength T is smaller (weaker) in S0s compared to spiral galaxies. Taken together, these results suggest that the stellar distribution in S0s is not drastically affected by the galaxy environment. However, some process inherent to the morphological transformation of spiral galaxies into S0s does affect stellar disc structure causing a weakening of μ(r) breaks and may even eliminate truncations from S0 galaxies. In further tests, we perform analytical bulge–disc decompositions on our S0s and compare the results to those for spiral galaxies from our previous studies. For type III galaxies, we find that bulge light can account for the excess light at large radii in up to ∼50 per cent of S0s but in only ∼15 per cent of spirals. We propose that this result is consistent with a fading stellar disc (evolving bulge-to-disc ratio) being an inherent process in the transformation of spiral galaxies into S0s.